Treatment of textile finishing wastewater using fenton's reagent - Aris, Azmi (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1999)
In this study, textile finishing wastewater was treated with Fenton's reagent (hydrogen peroxide-ferrous iron system). Under unstable and complex wastewater condition, Fenton's reagent was unable to comply with the standard set by the authority with respect to COD. How.ever, removal of SScomplies with the standard while visibility of the wastewater improves by more than 50 %. Removal was mainly by OH radical oxidation as compared to hydroxide precipitation. Mineralisation of more than 50 % organics was observed after 5 minutes reaction while 77 % mineralisation was observed after 30 minutes reaction . The amount of hydrogen peroxide and ferrous iron substantially affects the quality of the treated wastewater